Kierkegaard and The Logic of Insanity - Westphal, Merold (Religious studies, 1971)
Feigned madness can be a valuable asset. King David once used it to escape from the Philistines (I Sam. 21), and a twentieth century king, Pirandello's Henry IV pulled much the same trick on a modern philistine culture. Thrown from his horse and struck on the head while on his way to a masquerade party dressed as the Henry of Canossa's chill repentance, he had for twenty years insanely identified himself with the eleventh century monarch. At least this is what his family and the court they provided for his humour thought. As the play opens they are unaware that he has returned to sanity, but has continued to play Henry IV for the last eight of the twenty years, preferring the mad world in which he had lived to the sane world to which he would have to return.